A conceptual framework for Islamic architecture - Omer, Spahic (Alhassanain (p) Network for Islamic Heritage and Thought, 2017)
This book discusses a conceptual framework for Islamic architecture which renders Islamic architecture such a unique subject and much different from other architectural expressions. The issues that form the cornerstones of the conceptual framework for Islamic architecture are dealt with in the paper. The issues discussed are: tawhid (the idea of God’s Oneness), man as the vicegerent (khalifah) on earth and his relationship with environment, comprehensive excellence (ihsan), and Islam as the final and universal revelation. The method adopted in the paper is that the mentioned themes are firstly briefly discussed. That is then followed by exploring the implications of each theme for shaping the identity of Islamic architecture.